Pemilih â€Hijauâ€ di Kota Santri: Kasus Pemilu 2004 di Pekalongan - Basyar, M. Hamdan (Pusat Penelitian Politik, 2004)
The victory ofthe political party that carries the Islamic symbol or well known as the